Britannilactone 1-O-acetate induced ubiquitination of NLRP3 inflammasome through TRIM31 as a protective mechanism against reflux esophagitis-induced esophageal injury - Ju Liu; Yang Xiao; Qianfei Xu; Yunyan Xu; Manman Guo; Yun Hu; Yan Wang; Yi Wang (BMC, 2024)
Abstract Background Reflux esophagitis (RE) is a disease in which inflammation of the esophageal mucosa owing to the reflux of gastric contents into the esophagus results in cytokine damage. Britannilactone 1-O-acetate (Brt) has anti-inflammatory effects, significantly inhibiting the activation of the NLRP3 inflammasome, leading to a decrease in inflammatory factors including IL-1 β, IL-6, and TNF-α. However, the mechanism underlying its protective effect against RE-induced esophageal injury remains unclear. In the present study, we investigated the protective mechanism of TRIM31 against NLRP3 ubiquitination-induced RE both in vivo and in vitro. Methods A model of RE was established in vivo in rats by the method of "4.2 mm pyloric clamp + 2/3 fundoplication". In vitro, the mod was constructed by using HET-1A (esophageal epithelial cells) and exposing the cells to acid, bile salts, and acidic bile salts. The 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay was used to screen the concentration of administered drugs, and the viability of HET-1A cells in each group. HE staining was used to assess the degree of pathological damage in esophageal tissues. Toluidine blue staining was used to detect whether the protective function of the esophageal epithelial barrier was damaged and restored. The enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of IL-1 β, IL-6, and TNF-α factors in serum. Immunohistochemistry (IHC) was used to detect the expression level of NLRP3 in esophageal tissues. The molecular docking and Co-immunoprecipitation assay (Co-IP assay) were used to detect the TRIM31 interacts with NLRP3. Western blotting detected the Claudin-4, Claudin-5, The G-protein-coupled receptor calcium-sensitive receptor (CaSR), NLRP3, TRIM31, ASC, C-Caspase1, and Caspase1 protein expression levels. Results Brt could alleviate RE inflammatory responses by modulating serum levels of IL-1 β, IL-6, and TNF-α. It also activated the expression of NLRP3, ASC, Caspase 1, and C-Caspase-1 in HET-1A cells. Brt also attenuated TRIM31/NLRP3-induced pathological injury in rats with RE through a molecular mechanism consistent with the in vitro results. Conclusions Brt promotes the ubiquitination of NLRP3 through TRIM31 and attenuates esophageal epithelial damage induced by RE caused by acidic bile salt exposure. This study provides valuable insights into the mechanism of action of Brt in the treatment of RE and highlights its promising application in the prevention of NLRP3 inflammatory vesicle-associated inflammatory pathological injury. Graphical Abstract